Analisis Kepemimpinan Kepala Desa dalam Meningkatkan Pelayanan Publik di Desa Cikunir Kecamatan Singaparna Kabupaten Tasikmalaya - Gilang Nur Rahman Sidik; Nurdiana Mulyantini (International Forum of Researchers and Lecturers, 2024)
This research is motivated by the results of preliminary observations that there are still service programs that have not been realized according to the specified time. Most people feel that the services provided by the village head and his staff have not yet touched the real needs of the community. Lack of awareness from local village government officials in the service process. The method used is a qualitative descriptive research method. The population in this study was 8 people. The sampling technique used the total sample technique, thus the sample in this study was 8 people. The data collection technique used a questionnaire. The results of the study are as follows: The Leadership of the Head of Cikunir Village, Singaparna District, Tasikmalaya Regency in Activities So far, it has been in accordance with the main function of the leader by carrying out his leadership properly and correctly, meaning, based on the rules of the game that have been agreed upon and determined by the organization. such as the preparation of the vision and mission and goals of the organization, so that from planning to accountability is directed at the goals that have been set, becoming a motivator, decision maker, performance assessment, dynamic and catalyst for the organization, stabilizer and supervisor. The implementation of public services in Cikunir Village, Singaparna District, Tasikmalaya Regency, has been in accordance with the Decree of the Minister of Administrative and Bureaucratic Reform Number 63 of 2004 concerning Minimum Service Standards, such as in terms of transparency, accountability, conditional, participatory, equal rights, and balance of rights and obligations. The obstacles faced by the village head in improving public services in Cikunir Village, Singaparna District, Tasikmalaya Regency, are human resources, facilities and infrastructure, education and human resources skills. Efforts that have been made by the Village Head in Improving Public Services in Cikunir Village, Singaparna District, Tasikmalaya Regency, are improving the quality of human resources through education and training; adding/completing service facilities and infrastructure; and improving employee skills through on the job training.